STEREOTYPES, MYTHS AND ARCHETYPES OF MERCHANT`S IMAGE (Herald of Journalism, 2021)
The chronicle of the Great Silk Road, connecting ancient peoples and regions, is rich not only in secrets and unresolved riddles, but also in many legends and tales, partly contrived, part based on other people's assumptions, partly limited by the time, but undoubtedly played out the history he had planned role. The purpose of this article was to draw the attention of the scientific public to the importance of stereotypes, mythologies, and partly prevailing prejudices today, connected both. The importance thatis having an impact on the modern vision of ancient history and shaping today's relationshipswith the history of functioning and with the practice of further studying the Silk Road. The main idea of scientific research was an attempt to uncover the concepts of stereotypes and mythologies that, according to the author, are most suitable for the purpose of studying the images of both ancient merchants and the fate of the trade highway itself. The study is distinguished both by its undoubted novelty, and by its share of certain courage, where the author not only gives a review, but also tries to approach the background of many problems of the present. In the work on the material we used both methods of comparative analysis, means of linguistic comparative studies and the search for analogies, as well as content analysis of historical and modern materials from literature and the media. The article may be of certain interest both for scientists and direct participants in the modern market.